2019
DOI: 10.36497/jri.v39i1.38
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Carbon Monoxide Expiratory Air on Shisha Users and the Factors Affecting

Abstract: Background: Shisha is one method of consuming tobacco similar to cigarette but in a different form. Lately it became a trend in Indonesian people, especially teenagers, without knowing any hazards contained in shisha which could cause cancer or even death. Lack of study about shisha in Indonesia was the main reason to do this study so further impact of shisha could be understood. Methodology: This study was analytical observational with cross sectional design. Data of this study was obtained from examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Measurements of lung function and expiratory CO were carried out after the respondents were given treatment to smoke shisha, there was a significant increase in CO and a decrease in lung function before and after the intervention. 9 Soeroso et al, research also found a weak correlation between CO and peak expiratory flow, the higher the CO levels. Expiration will reduce peak expiratory flow (r=-0.26 and p=0.106).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Measurements of lung function and expiratory CO were carried out after the respondents were given treatment to smoke shisha, there was a significant increase in CO and a decrease in lung function before and after the intervention. 9 Soeroso et al, research also found a weak correlation between CO and peak expiratory flow, the higher the CO levels. Expiration will reduce peak expiratory flow (r=-0.26 and p=0.106).…”
Section: Discussionmentioning
confidence: 91%
“…In healthy populations who do not smoke, end-tidal concentrations are in the range of 1-3 ppm. 9 Carbon monoxide is one of the most widely distributed pollutants in the air. CO concentrations are released into the air in the highest quantities among other air pollutants every year except for carbon dioxide (CO2) concentrations.…”
Section: Introductionmentioning
confidence: 99%